Association of Gallbladder Polyp and Stroke: A Nationwide, Population-Based Study. Issue 48 (December 2015) - Chen, Chien-Hua; Lin, Cheng-Li; Kao, Chia-Hung
Abstract : Abstract: Gallbladder polyp (GP) and stroke share several metabolic disorders as risk factors. We assessed the association between GP and subsequent stroke risk. From 2000 to 2011, patients with GP aged >20 years were identified from the Longitudinal Health Insurance Database 2000. Of the 15, 975 examined patients, 12, 780 and 3195 were categorized into the non-GP and GP cohorts, respectively. The relative risks of stroke were estimated using the Cox proportional hazard model after adjusting for age, sex, and comorbidities. The overall incidence of stroke was higher in the GP cohort than in the non-GP cohort (6.66 vs 5.20/1000 person-yr), with an incidence rate ratio (IRR) of 1.28 (95% confidence interval [CI] = 1.15–1.42). The risk of stroke was 1.32-fold (95% CI = 1.06–1.63) in patients with GP compared with patients without GP after adjusting for age, sex, income level, urbanization level, occupation and comorbidities of gallstone, alcohol-related illness, diabetes, hyperlipidemia, hypertension, obesity, COPD, coronary heart disease, and asthma. Furthermore, the stroke risk was higher among elderly patients (with 1-yr intervals; adjusted HR [aHR] = 1.06, 95% CI = 1.05–1.07), the male sex (aHR = 1.62, 95% CI = 1.35–1.96), lower income level (aHR = 1.37, 95% CI = 1.02–1.85 for level I; aHR = 1.62, 95% CI = 1.25–2.10 for level II), living in second urbanized areas (aHR = 1.28, 95% CI = 1.00–1.63), alcohol-related illness (aHR = 1.56, 95% CI = 1.07–2.28), diabetes (aHR = 1.78, 95% CI = 1.41–2.24), and hypertension (aHR = 2.74, 95% CI = 2.19–3.42). GP is associated with stroke; however, GP may be less influential than other risk factors are, such as male sex, lower income level, alcohol-related illness, diabetes, and hypertension, on stroke development. Additional studies are required to clarify whether GP is a risk factor for or an epiphenomenon of stroke development.